PENELUSURAN AKUNTANSI DALAM KEHIDUPAN SEHARI-HARI MAHASISWA UNIVERSITAS BRAWIJAYA - Rahmi, Annisa; Mulawarman, Aji Dedi (Jurnal Ilmiah Mahasiswa FEB, 2016)
This study aims to explore how accounting practices in everyday life that present in the pop culture in students of Brawijaya University. The research is done by using a qualitative approach through ethnographic methods of Spradley version. This search noticed accounting practices that occur in everyday life of Brawijaya University students could lead to the accounting equation according to Brawijaya University students also unique and different meanings of accounting. The analysis of this research reinforces the theory and previous research that accounting is indeed present in everyday life. Daily life of students who is familiar with pop culture explain that the accounting is to affect and are affected by culture without any concern. Thus, accounting is not only in business perspective but also in the perspective of an accounting everyday life.Â  Keywords: Accounting in everyday life, pop culture, ethnography.